The Ocean Observatories Initiative - Trowbridge, John; Weller, Robert; Kelley, Deborah; Dever, Edward; Plueddemann, Albert; Barth, John A.; Kawka, Orest (Frontiers in Marine Science, 2019)
The Ocean Observatories Initiative (OOI) is an integrated network that enables scientific investigation of interlinked physical, chemical, biological and geological processes throughout the global ocean. With near real-time data delivery via a common Cyberinfrastructure, the OOI instruments two contrasting ocean systems at three scales. The Regional Cabled Array instruments a tectonic plate and overlying ocean in the northeast Pacific, providing a permanent electro-optical cable connecting multiple seafloor nodes that provide high power and bandwidth to seafloor sensors and moorings with instrumented wire crawlers, all with speed-of-light interactive capabilities. Coastal arrays include the Pioneer Array, a relocatable system currently quantifying the New England shelf-break front, and the Endurance Array, a fixed system off Washington and Oregon with connections to the Regional Cabled Array. The Global Arrays host deep-ocean moorings and gliders to provide interdisciplinary measurements of the water column, mesoscale variability, and air-sea fluxes at critical high latitude locations. The OOI has unique aspects relevant to the international ocean observing community. The OOI uses common sensor types, verification protocols, and data formats across multiple platform types in diverse oceanographic regimes. OOI observing is sustained, with initial deployment in 2013 and 25 years of operation planned. The OOI is distributed among sites selected for scientific relevance based on community input and linked by important oceanographic processes. Scientific highlights include real-time observations of a submarine volcanic eruption, time-series observations of methane bubble plumes from Southern Hydrate Ridge off Oregon, observations of anomalous low-salinity pulses off Oregon, discovery of new mechanisms for intrusions of the Gulf Stream onto the shelf in the Middle Atlantic Bight, documentation of deep winter convection in the Irminger Sea, and observations of extreme surface forcing at the most southerly surface mooring in the world ocean.